Electrocatalytic Production of C3‐C4 Compounds by Conversion of CO2 on a Chloride‐Induced Bi‐Phasic Cu2O‐Cu Catalyst. Issue 49 (16th October 2015) - Lee, Seunghwa; Kim, Dahee; Lee, Jaeyoung
Abstract: Electrocatalytic conversion of carbon dioxide (CO2 ) has recently received considerable attention as one of the most feasible CO2 utilization techniques. In particular, copper and copper‐derived catalysts have exhibited the ability to produce a number of organic molecules from CO2 . Herein, we report a chloride (Cl)‐induced bi‐phasic cuprous oxide (Cu2 O) and metallic copper (Cu) electrode (Cu2 OCl ) as an efficient catalyst for the formation of high‐carbon organic molecules by CO2 conversion, and identify the origin of electroselectivity toward the formation of high‐carbon organic compounds. The Cu2 OCl electrocatalyst results in the preferential formation of multi‐carbon fuels, including n ‐propanol and n ‐butane C3–C4 compounds. We propose that the remarkable electrocatalytic conversion behavior is due to the favorable affinity between the reaction intermediates and the catalytic surface. Abstract : Cl‐induced bi‐phasic Cu2 O–Cu shows remarkable catalytic ability for CO2 conversion toward high‐carbon‐number compounds. The oxidized Cu phase allows reaction intermediates to stay for a longer time on the surface, and consequently leads to formation of larger molecules.